Youth perceptions toward managing elderly care among low-income household families using the My-Elderly-Care-Skills Module - Mokhzan, Nur Syuhada; Sutan, Rosnah; Yasin, Ruhizan Mohammad; Yamat, Hamidah (Frontiers in Public Health, 2023)
Background: Caregivers of elderly people need the right education and empowering skills in managing the care of their own health needs and the elderly people whom they care for. Objective: This study aims to explore youth perception of the My-Elderly Skills Module intervention and its perceived acceptability in its implementation. Methods: This study involved youth respondents (18-30 years old) from a low-income household family who are accountable to provide care for independent older people (60 years and above) living in the same house. The study employed a nonrandomized quasi-experimental design. There were 30 youths selected as the intervention group (attended the My Elderly Skills online workshop for two days) and another 30 youths served as the control group (no intervention). The qualitative assessment of their perception was based on the content of the My Elderly Skills module, its implementation, and its usage in the care of the elderly. Data was recorded and transcribed verbatim before conducting theme analysis. Inductive content analysis was performed. Results: Thematic analysis generates four themes; i.e. knowledge competency, prioritizing elderly care needs, elderly health awareness, and enhancement program. Conclusion: The My-Elderly Skills training intervention has been verified to be effective in attracting youth caregivers of the elderly to participate in the training with an increase in knowledge and skills performance in managing and caring for the elderly.